2008
DOI: 10.1007/s00540-007-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane effect of lidocaine is inhibited by interaction with peroxynitrite

Abstract: Inflammation is clinically well known to decrease the efficiency of local anesthesia, an effect which has been explained mechanistically by tissue acidosis in the literature. However, recent studies offer no support to such a pharmacopathological background for anesthetic failure. Because inflammatory cells produce significant amounts of peroxynitrite, the peroxynitrite could interact with local anesthetics to decrease their effects. To examine this speculated interaction, we determined whether membrane fluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The present results suggest that infl ammatory peroxynitrite affects local anesthesia not only directly by interacting with lidocaine [9] but also indirectly by acting on nerve-cell membranes. Both the drug interaction and the membrane action would decrease the effi cacies of topical and infi ltration anesthesia, in which local anesthetics are applied into or close to infl amed tissues.…”
Section: Abstract Peroxynitrite · Lidocaine · Membrane Lipids · Fluimentioning
confidence: 89%
See 2 more Smart Citations
“…The present results suggest that infl ammatory peroxynitrite affects local anesthesia not only directly by interacting with lidocaine [9] but also indirectly by acting on nerve-cell membranes. Both the drug interaction and the membrane action would decrease the effi cacies of topical and infi ltration anesthesia, in which local anesthetics are applied into or close to infl amed tissues.…”
Section: Abstract Peroxynitrite · Lidocaine · Membrane Lipids · Fluimentioning
confidence: 89%
“…However, experimental verifi cations are challenging this mechanistic theory [7,8]. One alternative mechanism was proposed by focusing on peroxynitrite [9], which is produced by infl ammatory cells and is relevant to various diseases [10].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The following DPH fluorescence polarization measurements showed that the membrane-fluidizing effects of local anesthetics were inhibited by the peroxynitrite treatment. Such inhibitions are causable by peroxynitrite directly acting on anesthetic molecules [45] and indirectly on membrane lipids [46]. …”
Section: Change Of Membrane Interactivitymentioning
confidence: 99%
“…This depends on inflammation initiation and duration, and highly dependent on amount of recruited cells. Older studies have measured high hydrogen ion concentrations in inflamed tissue (down to pH 5.4), fracture related hematomas (down to pH 4.7), and in caridac ischemia (down to pH 5.7) . Indeed, our group has previously used AcDex for treating models of cardiac ischemia .…”
Section: Resultsmentioning
confidence: 99%